Perbandingan Reformasi Kepegawaian Negara Singapura dan Filipina - Daniel Pandapotan Siregar; Lina Miftahul Jannah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Each country has its own personnel reform. Starting from recruitment and selection to compensation given to civil servants. This article discusses civil service reform in Singapore and the Philippines. The two countries are ASEAN countries that are quite different in terms of their personnel reform. This is because Singapore is better known as a developed and prosperous country than the Philippines. This article takes data from supporting books, journals, papers, and internet searches, especially those related to the theory of personnel reform, recruitment, employee development, and compensation systems. The result of the comparison of reforms from the two countries is that Singapore is leading in most of the change processes in the process of achieving indicators in the bureaucratic reform program. Both in terms of human resource development, leadership and the form of governance principles adopted